2020
DOI: 10.3390/su12062240
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fertilizer Use in South China—Impacts and Implications on Smallholder Rice Farmers

Abstract: Despite the overuse of fertilizer in China, yields have stagnated while environmental pollution has risen. To increase sustainable production, the “Three Controls” Technology (3CT) was adopted in Guangdong Province as an agricultural best management practice for rice production. Its goal is to reduce the fertilizer use of farmers while decreasing the number of unproductive tillers and controlling pests and diseases. The objective of this study was to determine the farmers’ perception of 3CT focusing on three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Correspondingly, farmers also expressed that they found the combined recommendations specified under 1M5R, captured in the variable “ease of use,” easy to apply. This result is concurrent with results from other studies, where farmers also perceived the ease of use to be an important factor in the adoption of environmentally friendly rice cultivation practices in Vietnam (Tu et al, 2018) and also in the South Chinese province Guangdong, for the reduction of fertilizer use in rice farming (Wehmeyer et al, 2020). Benefit perceptions seem to play a significant role to follow 1M5R which is in line with results from a study investigating the acceptance of new rice straw management practices in the Mekong River Delta (Connor et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Correspondingly, farmers also expressed that they found the combined recommendations specified under 1M5R, captured in the variable “ease of use,” easy to apply. This result is concurrent with results from other studies, where farmers also perceived the ease of use to be an important factor in the adoption of environmentally friendly rice cultivation practices in Vietnam (Tu et al, 2018) and also in the South Chinese province Guangdong, for the reduction of fertilizer use in rice farming (Wehmeyer et al, 2020). Benefit perceptions seem to play a significant role to follow 1M5R which is in line with results from a study investigating the acceptance of new rice straw management practices in the Mekong River Delta (Connor et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…With regard to determine farmers’ reduction of post-harvest losses, they were asked if they have used a combine harvester since it has been shown that combine harvesters can reduce post-harvest losses (Praweenwongwuthi et al, 2010), if they have used solar bubble driers, flatbed driers, and different types of storage bags. Furthermore, farmers, who have adopted a practice or technology were asked to provide information about the reasons for adoption using 23 statements (Wehmeyer et al, 2020) (Figure 2) and for non-adoption of a practice or technology using 18 statements which farmers had to evaluate on a six-point Likert-type scale (1 = not applicable at all, 6 = very applicable) (Wehmeyer et al, 2020) (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has improved overall global agricultural productivity, crop yields, and soil fertility. As a result of increased fertilizer use, agriculture production, crop yield and soil fertility were increased globally (Wehmeyer, de Guia & Connor, 2020). Since its introduction during the Green Revolution in the 1960s, synthetic fertilizer has been an essential factor of Asian agriculture (Lu & Tian, 2017).…”
Section: Introductionmentioning
confidence: 99%